Deep Convolutional Level Set Method for Image Segmentation - Agustinus Kristiadi; Pranowo Pranowo (LPPM ITB, 2017)
Level Set Method is a popular method for image segmentation. One of the problems in Level Set Method is finding the right initial surface parameter, which implicitly affects the curve evolution and ultimately the segmentation result. By setting the initial curve too far away from the target object, Level Set Method could potentially miss the target altogether, whereas by setting the initial curve as general as possible